Mechanical caracterisation of polyester and sunflower natural fiber composite - Rocha, João (2013)
The use of natural fibers as reinforcement in polymer matrix composites is gaining popularity in the development of renewable products. Although glass and other synthetic fiber-reinforced plastics possess high specific strength, their fields of application are very limited because of their inherent higher cost of production. This work deals with the characteristics of natural fiber composites that can offer several advantages, like low cost, weight savings and relatively good mechanical properties. It focuses on the effects of sunflower fibers as reinforcement agents in composites. Mechanical testing of Sunflower natural fibers composite was performed to qualify and quantify the reinforcement properties. At same time, Glass fiber composite sample tests have been produced and characterized and both results have been compared. From results comparison we can affirm that the produced polymeric sunflower fiber composite has adequate mechanical properties for lots of industrial applications even, as expected, these are lower than glass fiber composites. Using this natural fiber content this product become a more ecological substitute and environment friendly that the traditional polymeric glass fiber composites. For other way, once stems from sunflower plants are wastes that traditionally are left in the field, shredded and incorporated in to the soil, acting like natural low cost substrate, by collecting them and giving them some commercial value will make crops more profitable.